1996
DOI: 10.1046/j.1365-2567.1996.508583.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of functional molecules by human CD3 decidual granular leucocyte clones

Abstract: SUMMARYCell surface and cytoplasmic antigen expression by 35 CD3 ÿ decidual granular leucocyte (DGL) clones, derived from human endometrial tissue in the first trimester of pregnancy, has been compared with both that of fresh CD3 ÿ decidual leucocytes and that of CD3 ÿ peripheral blood natural killer (PBNK) cell clones (n 12). The majority of DGL clones retained the antigenic phenotype of fresh cells, although CD103 (HML-1) was expressed on 50% of DGL clones but only 17% of fresh DGL. Both cytoplasmic CD3z and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The selection of patients and control was carried out by systematic random sample. The mean age of the patients was 26.85 years (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], and the average number of RM was 4 (range 3-6). All women selected were not having any previous live births (primary miscarriage).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of patients and control was carried out by systematic random sample. The mean age of the patients was 26.85 years (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], and the average number of RM was 4 (range 3-6). All women selected were not having any previous live births (primary miscarriage).…”
Section: Methodsmentioning
confidence: 99%
“…In the decidua, the area of the interface where foetomaternal interaction occurs, CD56-positive NK cells are the dominant type of lymphocytes and express CD94: NKG2A complex, suggesting that HLA-E protein on the trophoblasts can be recognized by the maternal immune cells. Thus, the expression of HLA-E might play a role in preventing the foetus from being attacked by maternal immune system [22]. Evidence showing lower expression of HLA-ER (0101) and its lower stability may impair its capability to downregulate NK cells and hence may be associated with RM [10].…”
Section: Hla-e Genotypesmentioning
confidence: 99%
“…The immunology of the fetomaternal interface has been studied extensively, particularly using sections derived from first trimester placenta or by the phenotypic analysis of isolated cells. The maternal part of the placenta consists of stromal cells, epithelial glandular cells, blood vessels, and numerous bone-marrow-derived cells, the main proportion of which are large granular lymphocytes with the phenotype CD3 Ϫ CD16 Ϫ CD56 ϩ and natural killer (NK) functions (Bulmer et al, 1991;Gudelj et al, 1996;King, 2000;King et al, 1989;Starkey et al, 1988). Other cells include macrophages (20%) and T cells (approximately 10%).…”
mentioning
confidence: 99%
“…Although further studies are required, decidual NK cells express MHC class I inhibitory receptors (9,25,26). Despite this, specificity and expression analyses have revealed that both types of inhibitory receptors are expressed on overlapping ''subsets'' of NK cells (7).…”
mentioning
confidence: 99%
“…Whether YT2C2 expresses an HLA-B-specific receptor, like NKAT3, is not yet known. Because it currently appears that CD94 associates with all known human lectin-like NK cell receptors and is expressed on all NK cells, including the vast majority of decidual NK cells (26), the lectin-like receptors were attractive candidate receptors for HLA-G in YT2C2. However, YT2C2 does not express CD94, excluding this possibility, but it is unknown if YT2C2 expresses NKG2 molecules, whether NKG2 could pair with molecules other than CD94, or even if the lectin-like receptors bind HLA-G.…”
mentioning
confidence: 99%